Integration of the calcium carbonate looping process into an existing pulverized coal-fired power plant for CO2 capture: Techno-economic and environmental evaluation. (15th July 2018) - Rolfe, A.; Huang, Y.; Haaf, M.; Rezvani, S.; MclIveen-Wright, D.; Hewitt, N.J.
Graphical abstract: Highlights: Technical results illustrated a 94% onsite CO2 capture ratio for the CCL unit. The CCL showed a lower efficiency penalty of 7.4% compared to solvent based system. The costs of CO2 captured and avoided were 16.3 and 20.3 €/tCO2, respectively. The integration of the CCL into a PC power plant nearly doubled the plant output. The LCA illustrated that the overall climate change impact had been reduced by 75%. Abstract: This work focuses on the techno-economic and environmental evaluation for an existing pulverised coal-fired power plant retrofitted with the calcium carbonate looping (CCL) process. The CCL process is an attractive technology due to relatively low efficiency penalties. To better understand the performance characteristics and benefits of systems integration, the steady-state model for the CCL process, developed in ECLIPSE, was used to perform a techno-economic analysis. The simulation results showed that the net efficiency for the selected 600 MW PC power plant equipped with the CCL process was 33.8% (lower heating value) at 94% CO2 capture ratio. With respect to the reference plant without CO2 capture, this resulted in a lower efficiency penalty (7.4% points). The capital cost and maintenance and operating costs were estimated according to a bottom-up approach using the information gained through the mass and energy balance. Specific investment was found to be €1778/kWe, which is approximately 21% higher than for the reference plant. The levelized cost of electricity would be €77.3/MWh with CCL CO2 capture. The CO2 capture cost and CO2 avoidance cost relative to the corresponding reference plant were €16.3/tCO2 captured and €22.3/tCO2 avoided, respectively. The SimaPro software was used to perform a life cycle analysis of the capture technology to determine its environmental impact. The results illustrated that the overall climate change impact had been reduced by 75%, while the fossil depletion impact was increased by 22%.